Born from lament : the theology and politics of hope in Africa - Katongole, Emmanuel, 1960- (William B. Eerdmans Publishing Company, 2017)
There is no more urgent theological task than to provide an account of hope in Africa, given its endless cycles of violence, war, poverty, and displacement. So claims Emmanuel Katongole, an innovative theological voice from Africa. In the midst of suffering, Katongole says, hope takes the form of "arguing" and "wrestling" with God. Such lament is not merely a cry of pain- it is a way of mourning, protesting, and appealing to God. As he unpacks the rich theological and social dimensions of the practice of lament in Africa, Katongole tells the stories of courageous Christian activists working for change in East Africa and invites readers to enter into lament along with them. --